Treatment of Chronic Refractory Pain by Combined Deep Brain Stimulation of the Anterior Cingulum and Sensory Thalamus (EMOPAIN Study): Rationale and Protocol of a Feasibility and Safety Study - Aurélie Leplus; Michel Lanteri-Minet; Anne Donnet; Nelly Darmon; Jean Regis; Denys Fontaine (Brain Sciences, 2022)
Background: Deep Brain Stimulation (DBS) of the sensory thalamus has been proposed for 40 years to treat medically refractory neuropathic pain, but its efficacy remains partial and unpredictable. Recent pilot studies of DBS targeting the ACC, a brain region involved in the integration of the affective, emotional, and cognitive aspects of pain, may improve patients suffering from refractory chronic pain. ACC-DBS could be complementary to thalamic DBS to treat both the sensory-discriminative and the affective components of chronic pain, but the safety of combined DBS, especially on cognition and affects, has not been studied. Methods: We propose a prospective, randomized, double-blind, and bicentric study to evaluate the feasibility and safety of bilateral ACC-DBS combined with unilateral thalamic DBS in adult patients suffering from chronic unilateral neuropathic pain, refractory to medical treatment. After a study period of six months, there is a cross-over randomized phase to compare the efficacy (evaluated by pain intensity and quality of life) and safety (evaluated by repeated neurological examination, psychiatric assessment, cognitive assessment, and assessment of affective functions) of combined ACC-thalamic DBS and thalamic DBS only, respectively. Discussion: The EMOPAIN study will show if ACC-DBS is a safe and effective therapy for patients suffering from chronic unilateral neuropathic pain, refractory to medical treatment. The design of the study will, for the first time, assess the efficacy of ACC-DBS combined with thalamic DBS in a blinded way.